BRIDGING CULTURES THROUGH AESTHETICS: A CROSS-CULTURAL JOURNEY INTO TRADITIONAL CHINESE ART - Müller, Anna (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
Cross-cultural communication plays an integral role in our daily interactions, enabling the exchange of knowledge, information, ideas, emotions, and beliefs across diverse social contexts. Within this intricate web of communication, intercultural encounters are common, forming the basis for international relations. A fundamental aspect of these relations is fostering goodwill among people. Strengthening cultural exchanges between Eastern and Western cultures not only allows for a mutual appreciation of each other's beauty but also facilitates the presentation of the finest aspects of their respective countries. In this context, the creation of artworks emerges as a primary avenue for showcasing China's image and reinforcing confidence in its rich culture. Effective cross-cultural communication necessitates a nuanced approach, characterized by meticulous translation, respect for historical truths, and the portrayal of distinct national characteristics. These measures collectively aim to dispel outdated stereotypes and misconceptions that persist in the modern world. This paper is dedicated to the analysis of traditional Chinese aesthetics, unveiling their manifestations, and offers insightful recommendations for enhancing cross-cultural communication.